Predatory Trading - BRUNNERMEIER, MARKUS K.; PEDERSEN, LASSE HEJE (Journal of Finance, 2005)
ABSTRACT This paper studies predatory trading , trading that induces and/or exploits the need of other investors to reduce their positions. We show that if one trader needs to sell, others also sell and subsequently buy back the asset. This leads to price overshooting and a reduced liquidation value for the distressed trader. Hence, the market is illiquid when liquidity is most needed. Further, a trader profits from triggering another trader's crisis, and the crisis can spill over across traders and across markets.